Potential protective benefits of Schisandrin B against severe acute hepatitis in children during the COVID-19 pandemic based on a network pharmacology analysis - Fang, Yanhua; Zhang, Lingling; Wang, Zhe; Wang, Ruoyu; Liang, Shanshan (Frontiers in Pharmacology, 2022)
Aims: Reports of hepatitis in children during the coronavirus disease 2019 (COVID-19) pandemic garnered worldwide attention. The most probable culprits are adenovirus and severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). At present, the optimal symptomatic treatment consists of a combination of anti-COVID-19 and hepatitis symptom alleviators. Schisandrin B (SchB) has been known to have liver-protective properties for a long time, whereas anti-COVID-19 properties only recently have been discovered. In the case of COVID-19 with hepatitis of unknown origin, we used network pharmacology to explore the symptomatic therapy and protective effects of SchB. Main methods: The most probable protein targets of SchB were predicted in the SwissTargetPrediction database. The GeneCards, National Center for Biotechnology Information, and Online Mendelian Inheritance in Man databases were used to compile information on the diseases hepatitis, adenovirus, and SARS-CoV-2. Following the use of a Venn diagram viewer to identify intersection genes, we constructed a protein–protein interaction network and identified the core genes. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment, as well as molecular docking, were employed to highlight the mechanisms of SchB on hepatitis. Key findings: SchB contains 27 targets on adenovirus_hepatitis and 16 targets on SARS-CoV-2_hepatitis, with 12 shared genes. Both target populations clustered in viral infection and cancer pathways, as well as in processes such as kinase activity phosphatase, cell adhesion, and ATPase binding. These genes might be closely related to liver damage and membrane binding from adenovirus or SARS-CoV-2 infections. In addition, epidermal growth factor receptor, HSP90AA1, and MAPK1 were among the top five targets of both SchB SARS-CoV-2 hepatitis and SchB adenovirus hepatitis. Significance: SchB may target common protective targets and mechanisms against acute hepatitis caused by adenovirus or by SARS-CoV-2 in children during the COVID-19 pandemic. These findings indicate SchB’s potential as a treatment for hepatitis of unknown origin.